IMPLEMENTASI PEMBELAJARAN UNTUK ANAK USIA DINI PADA MASA PANDEMI DI PAUD TERPADU AISYIYAH BANGKA BARAT - Sari, Anggreani Putri (ICEJ : Islamic Childhood Education Journal, 2022)
The impact of Covid-19 is very much felt in the field of learning, especially in education which requires learning to be done from home and the implementation of learning for early childhood during the pandemic. This study examines two aspects, namely: first, how the implementation of learning for Early Childhood during the pandemic at PAUD Terpadu Aisyiyah West Bangka. Second, what are the factors that support and hinder learning inhibition for Early Childhood during the pandemic at PAUD Terpadu Aisyiyah West Bangka. This research is a qualitative field research. Based on the results of the study, the implementation of learning for early childhood during the pandemic at PAUD Terpadu Aisyiyah West Bangka, includes: planning, implementation and evaluation. The supporting factors are providing facilities for educators and parents in the form of internet quotas, the availability of facilities and infrastructure for learning so that it is carried out effectively and efficiently. Inhibiting factors such as children are easily bored, lazy, and not serious in learning. The signal is not stable, the implementation time coincides with the parents’ working hours, so that parents cannot accompany students to study.